2014
DOI: 10.1021/la503437a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lipid Coatings on Surface Wettability Characteristics of Silicone Hydrogels

Abstract: Insoluble lipids serve vital functions in our bodies and interact with biomedical devices, e.g., the tear film on a contact lens. Over a period of time, these naturally occurring lipids form interfacial coatings that modify the wettability characteristics of these foreign synthetic surfaces. In this study, we examine the deposition and consequences of tear film lipids on silicone hydrogel (SiHy) contact lenses. We use bovine meibum, which is a complex mixture of waxy esters, cholesterol esters, and lipids that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…First, there may be significant differences between the tear film lipid layer and meibum spread on saline which cause a difference in evaporation resistance. Second, despite the findings of Mishima and Maurice (1961), the tear film lipid layer may have little or no effect on evaporation and tear film thinning, implying that tear film instability may have another cause, e.g., related to the viscoelastic properties of the lipid layer (Bhamla et al, 2014; Georgiev et al, 2014). …”
Section: Interblinkmentioning
confidence: 91%
See 2 more Smart Citations
“…First, there may be significant differences between the tear film lipid layer and meibum spread on saline which cause a difference in evaporation resistance. Second, despite the findings of Mishima and Maurice (1961), the tear film lipid layer may have little or no effect on evaporation and tear film thinning, implying that tear film instability may have another cause, e.g., related to the viscoelastic properties of the lipid layer (Bhamla et al, 2014; Georgiev et al, 2014). …”
Section: Interblinkmentioning
confidence: 91%
“…In observations of the lipid layer, it is not uncommon to see more lipid left behind in central regions of the cornea during the upstroke which subsequently spreads. The dynamics and mechanisms of this lipid motion are an area of considerable interest (Aydemir et al, 2011; Bhamla et al, 2014; Bruna and Breward, 2014; King-Smith et al, 2013a; Rosenfeld et al, 2013). …”
Section: Upstrokementioning
confidence: 99%
See 1 more Smart Citation
“…31 Dewetting of the tear film may also transfer the lipid onto the underlying lens substrate, resulting in fouling of the lens surface. This fouling can modify the lens surface wettability 32 with acute ophthalmologic consequences for the lens wearer, including inflammatory disorders, reduced vision, and symptoms of dry eye. 2,8,33 A photograph and schematic of the instrument is seen in Figure 2.…”
Section: Experimental Setup: I-ddropmentioning
confidence: 99%
“…Past work has shown that the dewetting mechanism results in transfer of the insoluble lipids at the moving contact line and subsequent fouling of the SiHy surface, ultimately affecting the lens wettability. 31,32 The whole dewetting process takes~5 minutes, leaving behind a dry SiHy surface that is fouled with a meibum layer.…”
Section: Surface Shear Rheologymentioning
confidence: 99%